2012
DOI: 10.5507/bp.2011.048
|View full text |Cite
|
Sign up to set email alerts
|

The value of <sup>18</sup>F-FDG PET/CT in assessment of metabolic response in esophageal cancer for prediction of histopathological response and survival after preoperative chemoradiotherapy

Abstract: Aim.To evaluate the ability of hybrid 18 F-fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) to predict histopathological response and overall survival (OS) after preoperative neoadjuvant chemoradiotherapy (CRT) in patients with the esophageal carcinoma. Methods. 73 patients with locally advanced esophageal carcinoma were included in the study. All were treated with CRT and 34 subsequently underwent surgical resection of the esophagus. 18F-FDG PET/CT was carried out prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 46 publications
1
16
1
Order By: Relevance
“…In contrast to the current study and other published reports, some studies demonstrated that FDG-PET did not effectively correlate with tumor response and long-term survival in patients with LAEC undergoing neoadjuvant CRT [17,25,26]. Malik et al [25 ]explained the possible reason of these discordant results.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In contrast to the current study and other published reports, some studies demonstrated that FDG-PET did not effectively correlate with tumor response and long-term survival in patients with LAEC undergoing neoadjuvant CRT [17,25,26]. Malik et al [25 ]explained the possible reason of these discordant results.…”
Section: Discussioncontrasting
confidence: 56%
“…Several previous studies investigated the predictive and prognostic role of sequential F-18 FDG PET/CT for metabolic tumor response and survival in LAEC treated preoperatively by CRT and revealed conflicting results [17,18,19,20,21,22,23,24,25,26,27,28]. Most of these studies used the SUV max values for the prediction of metabolic response and survival in LAEC patients.…”
Section: Discussionmentioning
confidence: 99%
“…As a semi-quantitative parameter of 18 F-FDG PET, SUV, which may reflect the intensity of metabolic activity of the tumor, has been suggested as a prognostic marker for the histopathological response of esophageal carcinoma (4)(5)(6)(7)(8)(17)(18)(19)(20). For example, Wieder et al (7) reported that, for histopathological responders, the decrease in SUV between baseline and 2 weeks after initiation of therapy was 44%, but was only 21% in the non-responders (P=0.0055).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports on determining the effect of CRT on esophageal carcinoma with F18-FDG PET have been published [26]. Similarly, it has reported that depending on the determination of the effect of CRT on other organs with DWMRI and tumor ADC increases in responders [15,16].…”
Section: Discussionmentioning
confidence: 99%